Scientific schools as a source of development of corporate culture in pedagogical university (Pedagogy of Higher and Secondary Education, 2013)
Koycheva T. I. Scientific schools as a source of development of corporate culture in pedagogical university.The article deals with the interpretation of the phenomenon of modern scientific school, justify her role in the innovative development of the university, in the formation and development of the corporate culture of Pedagogical University.
Keywords: Scientific School; Pedagogical University; corporate culture; innovative development